Better efficacy of triple antibiotics therapy for human brucellosis: A systematic review and meta-analysis. - Shanjun Huang; Hao Wang; Fande Li; Lanping Du; Wenqi Fan; Meifang Zhao; Hua Zhen; Yuke Yan; Menghan Lu; Xin Han; Zhuo Li; Mujinyan Li; et al. (PLoS Neglected Tropical Diseases)
Background The treatment of brucellosis suffers from a high recurrence rate and drug resistance. Our study researched the differences in efficacy and side effects between triple antibiotics therapy and dual antibiotics therapy in the treatment of brucellosis through a systematic review and meta-analysis. Methods We searched 4 English electronic databases and 2 Chinese electronic databases for randomized controlled trials and cohort studies published through September 2022 on the use of triple antibiotics versus dual antibiotics in the treatment of brucellosis. Overall outcome indicators were therapeutic failure rate, relapse rate, overall therapeutic failure rate, and side effect rate. Relative risk (RR) and 95% confidence intervals (95% CIs) were used as summary statistics. A fixed-effects model was used to combine the overall effect sizes. Results The meta-analysis included 15 studies consisting of 11 randomized controlled trials and 4 cohort studies. Triple antibiotics showed better efficacy than dual antibiotics in a comparison of 3 overall outcome indicators (therapeutic failure rate (RR 0.42; 95% CI 0.30 to 0.59 heterogeneity P = 0.29, I2 = 15%), relapse rate (RR 0.29; 95% CI 0.18 to 0.45 heterogeneity P = 0.88, I2 = 0%), and overall therapeutic failure rate (RR 0.37; 95% CI 0.28 to 0.48 heterogeneity P = 0.35, I2 = 9%)). The incidence of side effects in patients with brucellosis treated with triple antibiotics was not significantly different from that in brucellosis patients treated with dual antibiotics (RR 0.85; 95% CI 0.67 to 1.06 heterogeneity P = 0.1, I2 = 35%). Sensitivity analyses showed robust results and Peter's test showed no publication bias. The results of subgroup analyses for the research type, drugs, and type of brucellosis were largely consistent with the overall outcome indicators, indicating the reliability and robustness of the overall results. Conclusions In the treatment of brucellosis, triple antibiotics have better efficacy than dual antibiotics and do not increase the incidence of side effects.